Applicability of Lean Healthcare in the emergency medical service (Research, Society and Development, 2023)
Introduction: The constant changes in the market and in organizations demanded that companies adapt to meet the needs of consumers. Within this process, lean emerges as an alternative management tool, bringing in its principles the reduction of waste, costs and risks, in addition to providing an improvement in the quality of service delivery. Objective: To synthesize the evidence of the applicability of the Lean Healthcare method in the medical emergency sector. Methods: This is an integrative review of literature of an applied nature on the Lean Healthcare method in the health sector.  Data collection was performed in the databases from January 2021 to April 2022 using a structured form with specifications according to its title, authors and year, methodological approach and contribution of the study. Results: it was found through the research that the successful application of the Lean Healthcare method in the emergency department is a major contributing factor in management, solving deficiencies faced in this scenario and providing strategies to improve the efficiency of service delivery to patients. The surveyed authors are unanimous when reporting that the method allows care to flow satisfactorily, but there is a need for all sectors of the hospital to adopt it. Conclusion: The studies showed that, although the applicability of Lean Healthcare is unquestionable, there is a need for further research focused on the real analysis of its effectiveness in emergency medical departments so that its effects can be thoroughly drawn in the literature.